Method for producing graphite-containing refractories

By embedding a carbon fiber fabric with optimized adhesive bonding within graphite-containing refractories, the method enhances durability and fracture energy, addressing the durability issues of refractories under extreme temperature fluctuations in steelmaking vessels.

JP7607605B2Active Publication Date: 2024-12-27JFE STEEL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022034471
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-07
Publication Date
2024-12-27
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

Existing refractories used in steelmaking vessels and hot metal pretreatment vessels lack sufficient durability under conditions of extreme temperature fluctuations and large internal temperature gradients, leading to reduced mechanical strength and increased fracture risk.

Method used

A manufacturing method involving the embedding of a carbon fiber fabric woven in multiple directions within a graphite-containing refractory material, using an adhesive to bond the fabric to the refractory, ensuring a specific area ratio and spacing of the carbon fiber bundles, and optimizing the adhesive's residual carbon content to enhance fracture energy and durability.

Benefits of technology

The method produces graphite-containing refractories with significantly improved fracture energy and durability, capable of withstanding harsh conditions with repeated temperature changes, particularly in tuyere bricks and other steelmaking equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607605000017
    Figure 0007607605000017
  • Figure 0007607605000018
    Figure 0007607605000018
  • Figure 0007607605000019
    Figure 0007607605000019
Patent Text Reader

Abstract

To provide a graphite-containing refractory which can obtain high durability even if it is used under a condition that temperature rise and temperature fall are repeated over a long period, like a lining refractory such as a converter and a molten iron preliminary treatment vessel.SOLUTION: A method for manufacturing a graphite-containing refractory in which carbon fiber fabrics B are embedded inside a refractory raw material A containing graphite includes: a preparation step of bonding an adhesive c to the carbon fiber fabrics B; and a molding step of embedding the carbon fiber fabrics B having completed the preparation step inside the refractory raw material A, molding the refractory raw material A where the carbon fiber fabrics B are embedded so as to obtain a refractory molding x, wherein in the refractory molding x obtained in the molding step, a gap of the neighboring carbon fiber bundles b in the same direction which constitute the carbon fiber fabrics B is larger than a maximum particle diameter of an aggregate constituting the refractory body A, in a cross section of the refractory molding in a plane direction of the carbon fiber fabrics B, an area ratio occupied by the carbon fiber fabrics B to the cross-sectional area of the refractory molding is 20% or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a graphite-containing refractory material in which a carbon fiber fabric formed by weaving carbon fiber bundles is disposed inside a refractory body. [Background technology]

[0002] The equipment used in the iron-making and steel-making processes in steelworks (refining vessels, transport vessels, and other steelmaking vessels) is lined with refractories to withstand long-term use at high temperatures. In general, magnesia-carbon refractories are used for the lining of converters used in the refining process, while alumina-silicon carbide-carbon refractories are used for the lining of torpedoes and blast furnace ladles used in the molten iron pretreatment process. The refractories used for lining these refining vessels and transport vessels are used under extremely harsh conditions, including mechanical shock from the charges, abrasion from stirring of molten steel and molten slag, slag erosion from molten slag, and sudden temperature changes during operation. For this reason, in order to ensure stable operation, it is necessary to use refractories with high durability that can withstand such harsh conditions.

[0003] In particular, the tuyere bricks that make up the tuyere portion of a converter have room temperature gas (oxygen, cooling hydrocarbon gas, etc.) flowing inside, and the inner surface near the inside of the furnace is cooled by the room temperature gas while the outer surface is exposed to high temperatures due to heat transfer from the molten steel in the furnace, so the thermal gradient inside the tuyere bricks is extremely large, and moreover, every time blowing of one charge of the converter is completed, the temperature drops due to the discharge of the molten steel, and large thermal fluctuations are repeated. The tuyere bricks installed in converters are used as frequently as about 2500 to 4000 charges, and are used under extremely harsh conditions where the situation where the above-mentioned large thermal gradient occurs and large thermal fluctuations are repeated for each charge, so they are required to have high durability to withstand use under such conditions. In addition, the refractory linings of the converter other than the tuyere bricks (the bricks that make up the inner wall of the converter) are also used under extremely harsh conditions where large thermal fluctuations as described above are repeated, so they are required to have high durability, although not as high as the tuyere bricks. Similarly, the refractory linings of molten iron pretreatment vessels such as torpedoes and blast furnace ladles, and ladle vessels are required to have high durability because they are used under extremely severe conditions where large thermal fluctuations are repeated.

[0004] As a technology for improving the durability of refractories, Patent Document 1 describes a method of impregnating high-strength fiber bundles with synthetic resin or pitch, and then subjecting them to a hardening process such as heat treatment to obtain a rod-shaped or mesh-shaped solidified body, which is then placed inside the refractory. Since the solidified high-strength fiber bundles are placed inside the refractory without losing their shape, it is said that the mechanical strength and spalling resistance of the refractory can be improved. Patent Document 2 also describes a technique in which a unidirectional bundle or fabric made of fibers having a higher tensile strength than the refractory is bonded to a part or the entire surface of a refractory with a heat-resistant adhesive, and claims that this technique can maintain the refractory at a high strength for a long time, improve the tensile strength of the refractory, suppress cracking and destruction, and improve the life and reliability of the refractory. Specifically, it describes a technique in which a bundle or fabric of fibers is bonded to a nozzle through which molten steel flows, such as a long nozzle, a submerged nozzle, or a sliding nozzle used in a continuous casting process of steel, in a direction that restrains the outer surface of the nozzle, and an oxidation prevention base layer or an oxidation prevention layer is disposed on the surface. In these nozzles, the bundle or fabric of fibers restrains the thermal expansion toward the outer surface when molten steel flows through the nozzle, and compressive stress is generated in the refractory constituting the nozzle, which is thought to suppress the occurrence of cracks and destruction. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-320196 A [Patent Document 2] JP 2007-106618 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, as a result of investigations conducted by the present inventors, it was found that even if carbon fibers are arranged in a refractory material in the form shown in Patent Documents 1 and 2, sufficient durability is not obtained for the refractory material to be used in steelmaking vessels (such as converters and molten iron pretreatment vessels) exposed to the harsh conditions described above. In addition, the technology described in Patent Document 1 involves placing a rod-shaped or mesh-shaped solidified body made by solidifying high-strength fiber bundles with resin, pitch, etc. inside a refractory material. Therefore, when the refractory raw materials are molded or constructed by compression molding or pouring, the solidified body acts as resistance, preventing the uniform compression and flow of the refractory raw materials, resulting in a decrease in the strength and breaking energy of the refractory material and a decrease in its durability.

[0007] In addition, in the continuous casting process in which the nozzle described in Patent Document 2 is used, multiple charges of molten steel blown in a converter are continuously cast, so the temperature change cycle of the nozzle used is longer than that of the refractory lining of the converter, hot metal pretreatment vessel, etc., and since the outer surface of the nozzle is subjected to radiation from the molten steel stored in the downstream vessel located below, the temperature difference with the molten steel flowing inside the nozzle is not so large. In contrast, the refractory lining of the converter, hot metal pretreatment vessel, etc. (particularly the tuyere bricks constituting the tuyere part of the converter) is used under very severe conditions as described above, and the inventors have found that the technology described in Patent Document 2 cannot sufficiently improve the durability of such refractories.

[0008] Therefore, an object of the present invention is to solve the problems of the conventional techniques as described above and to provide a method for stably producing a graphite-containing refractory which has high durability even when used under conditions in which heating and cooling are repeated over a long period of time, such as the lining refractory material for converters and molten iron pretreatment vessels, and which has high durability even when used under conditions in which the internal temperature gradient is extremely large, such as tuyere bricks for converters. [Means for solving the problem]

[0009] As a result of extensive investigations aimed at solving the above problems, the inventors have found that by embedding a specific carbon fiber fabric having an adhesive attached thereto in a predetermined form inside the refractory raw material, and preferably optimizing the fiber diameter and number of the carbon fibers constituting the carbon fiber fabric, and further the density of the carbon fibers in the cross section of the refractory, the fracture energy of the refractory can be significantly improved compared to conventional techniques, and high durability can be obtained even in the above-mentioned extremely severe usage environments. The present invention has been made based on these findings, and has the following gist.

[0010] [1] A method for producing a graphite-containing refractory, comprising embedding a carbon fiber fabric (B) in which carbon fiber bundles (b) are woven in two or more directions inside a graphite-containing refractory raw material (A), comprising: A preparation step (i) of attaching an adhesive (c) to a carbon fiber fabric (B); a molding step (ii) of embedding the carbon fiber fabric (B) to which the adhesive (c) has been attached in the preparation step (i) inside a refractory raw material (A) and molding the refractory raw material (A) in which the carbon fiber fabric (B) is embedded to obtain a refractory molded body (x); The refractory molding (x) obtained in the molding step (ii) is characterized in that the interval between adjacent carbon fiber bundles (b) in the same direction constituting the carbon fiber fabric (B) is larger than the maximum grain size of the aggregate constituting the refractory raw material (A), and in the cross section of the refractory molding in the plane direction of the carbon fiber fabric (B), the area ratio of the carbon fiber fabric (B) to the cross-sectional area of ​​the refractory molding is 20% or more.

[0011] [2] In the manufacturing method of the above [1], in the preparation step (i), the adhesive (c) is adhered to the outer surface of the carbon fiber fabric (B) and is allowed to penetrate into the bundles of carbon fiber bundles (b) constituting the carbon fiber fabric (B); The method for producing a graphite-containing refractory material is characterized in that the refractory molding (x) obtained in the molding step (ii) comprises an embedded carbon fiber fabric (B) containing an adhesive (c) in a bundle of carbon fiber bundles (b) and being adhered or bonded to the refractory raw material (A) via the adhesive (c). [3] The method for producing a graphite-containing refractory material according to the above [1] or [2], further comprising a drying step (iii) of drying the refractory molding (x) obtained in the molding step (ii). [4] The method for producing a graphite-containing refractory material, in any one of the above-mentioned [1] to [3], wherein the adhesive (c) is one or more selected from the group consisting of an organic resin solution, an inorganic sol, tar, pitch, and an organic glue.

[0012] [5] The method for producing a graphite-containing refractory, wherein in any one of the production methods [1] to [4] above, in the refractory molding (x) obtained in the molding step (ii), the carbon fiber fabric (B) is embedded along a direction perpendicular to a working surface of the refractory. [6] The method for producing a graphite-containing refractory material according to any one of the above-mentioned [1] to [5], wherein the carbon fiber fabric (B) has a thickness of 0.1 mm or more and 3 mm or less.

[0013] [7] The method for producing a graphite-containing refractory material according to any one of the above-mentioned [1] to [6], wherein the refractory molding (x) obtained in the molding step (ii) has two or more layers of the carbon fiber fabric (B) embedded therein at intervals. [8] The method for producing a graphite-containing refractory material according to the above [7], wherein two or more layers of the carbon fiber fabric (B) are embedded in parallel at intervals, and the interval between adjacent carbon fiber fabrics (B) is 10 mm or more. [9] The method for producing a graphite-containing refractory material, in any one of the production methods [1] to [8] above, wherein the carbon fiber bundles (b) constituting the carbon fiber fabric (B) are arranged in the same direction, and the interval between adjacent carbon fiber bundles (b) exceeds 3 mm.

[0014]

[10] The method for producing a graphite-containing refractory material according to any one of the above [1] to [9], wherein the carbon fiber bundles (b) constituting the carbon fiber fabric (B) have a width of more than 1 mm and not more than 15 mm.

[11] The method for producing a graphite-containing refractory material, in any one of the above-mentioned methods [1] to

[10] , wherein the adhesive (c) contains an organic substance having a residual carbon rate of 6 mass% or more and 80 mass% or less.

[12] The method for producing a graphite-containing refractory, in any one of the production methods [1] to

[11] above, wherein the refractory raw material (A) has a graphite raw material content of 1 mass% or more and 80 mass% or less.

[13] The method for producing a graphite-containing refractory, in any one of the production methods [1] to

[12] above, wherein the refractory raw material (A) has a magnesia raw material content of 20 mass% or more and 99 mass% or less.

[0015]

[14] The method for producing a graphite-containing refractory, in any one of the production methods [1] to

[13] above, wherein the refractory raw material (A) has an alumina raw material content of 10 mass% or more and 95 mass% or less.

[15] The method for producing a graphite-containing refractory material, in any one of the above-mentioned production methods [1] to

[12] and

[14] , characterized in that the refractory raw material (A) has a silica raw material content of 1 mass% or more and 50 mass% or less.

[16] The method for producing a graphite-containing refractory material according to the above

[14] or

[15] , wherein the refractory raw material (A) has a silicon carbide raw material content of 1 mass% or more.

[17] In any one of the above-mentioned manufacturing methods [1] to

[16] , the refractory raw material (A) contains refractory shavings obtained by pulverizing used refractories in an amount of 10 mass% or more and 90 mass% or less as the refractory raw material. Effect of the Invention

[0016] According to the present invention, it is possible to stably produce a graphite-containing refractory which has high fracture energy and therefore has high durability even when used under conditions in which heating and cooling are repeated over a long period of time, such as the lining refractory material of a converter or a molten iron pretreatment vessel, and which has high durability even when used under conditions in which the internal temperature gradient is particularly large, such as the tuyere bricks of a converter. [Brief description of the drawings]

[0017] [Figure 1] A flow chart showing an example of a process for producing a graphite-containing refractory material according to the present invention. [Diagram 2] FIG. 2(a) is a side view of an example of a graphite-containing refractory produced by the method of the present invention, and FIG. 2(b) is a cross-sectional view taken along line II-II in FIG. 2(a) (a cross-sectional view parallel to the operating surface of the refractory). [Diagram 3] Cross-sectional view along line III-III in Figure 2(A) (cross-sectional view of the refractory in the plane direction of carbon fiber fabric B) [Figure 4] FIG. 4(A) is an explanatory diagram showing a method for measuring the bending strength of a graphite-containing refractory in an embodiment, and FIG. 4(B) is an explanatory diagram showing an end face of a test piece in FIG. 4(A). [Diagram 5] FIG. 1 is a diagram showing an example of fracture energy calculated from a load-displacement curve obtained in a three-point bending strength test in an embodiment. [Figure 6] FIG. 6 shows a test method for evaluating the corrosion resistance of a graphite-containing refractory material in the examples. FIG. 6(A) is an explanatory diagram showing the test furnace and a cylindrical sample in vertical section as the test is carried out. FIG. 6(B) is a plan view of the cylindrical sample shown in FIG. 6(A). FIG. 6(C) is a perspective view showing one of the test pieces constituting the cylindrical sample shown in FIGS. 6(A) and (B). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The manufacturing method of the present invention is a method for manufacturing a graphite-containing refractory in which a carbon fiber fabric B, in which carbon fiber bundles b are woven in two or more directions, is embedded inside a refractory raw material A containing graphite, and includes a preparation step (i) of adhering an adhesive c to the carbon fiber fabric B, and a molding step (ii) of embedding the carbon fiber fabric B to which the adhesive c has been adhered in the preparation step (i) inside the refractory raw material A and molding the refractory raw material A in which the carbon fiber fabric B is embedded to obtain a refractory molded body x, and the refractory molded body x obtained in the molding step (ii) is characterized in that the interval between adjacent carbon fiber bundles b in the same direction that constitute the carbon fiber fabric B is larger than the maximum grain size of the aggregate that constitutes the refractory raw material A, and in the cross section of the refractory molded body in the plane direction of the carbon fiber fabric B, the area ratio of the carbon fiber fabric B to the cross-sectional area of ​​the refractory molded body is 20% or more.

[0019] In the graphite-containing refractory produced by the method of the present invention, the carbon fiber fabric B disposed (embedded) inside the refractory raw material A is bonded or adhered to the refractory raw material A via the adhesive c, so that the carbon fiber fabric B is integrated with the refractory, and in addition, a specific carbon fiber fabric is embedded in the refractory raw material in a predetermined form, so that a high fracture energy capable of suppressing the occurrence of cracks can be obtained. Also, in the preparation step (i), not only is the adhesive c attached to the outer surface of the carbon fiber fabric B, but the adhesive c is also permeated (impregnated) into the bundles of carbon fiber bundles b constituting the carbon fiber fabric B, so that the carbon fiber bundles b are integrated as bundles by the adhesive c, so that a higher fracture energy can be obtained.

[0020] FIG. 1 shows an example of a manufacturing process of a graphite-containing refractory by the method of the present invention. FIG. 2 and FIG. 3 are schematic diagrams of an example of a graphite-containing refractory manufactured by the method of the present invention, in which FIG. 2(A) is a side view, FIG. 2(B) is a cross-sectional view along line II-II in FIG. 2(A) (cross-sectional view parallel to the refractory working surface), and FIG. 3 is a cross-sectional view along line III-III in FIG. 2(A) (cross-sectional view of the refractory in the plane direction of carbon fiber fabric B). In the figure, s1 is the working surface of the refractory (surface that contacts molten steel or slag), and s2 is the counter-working surface. In this graphite-containing refractory, three layers of carbon fiber fabric B are arranged (embedded) in parallel at a predetermined interval inside the refractory body (part composed of refractory raw material A; the same applies below). In the preparation step (i), an adhesive c is applied to the carbon fiber fabric B. At this time, in order to bond or adhere the carbon fiber fabric B and the refractory raw material A together to integrate them, the adhesive c is applied so as to cover the outer surface of the carbon fiber fabric B, and more preferably, in order to integrate the carbon fiber bundles b constituting the carbon fiber fabric B as bundles, the adhesive c is allowed to penetrate (impregnate) into the carbon fiber bundles b (gaps between the carbon fibers).

[0021] The adhesive c is preferably one that contains an organic substance such as an organic resin and / or inorganic fine particles such as alumina or silica (that is, an adhesive that contains an organic substance and / or inorganic fine particles as active ingredients). As shown in Fig. 3, the adhesive c covers the outer surface of the carbon fiber fabric B (carbon fiber bundles b) inside the refractory raw material A (refractory body) to adhere or bond the carbon fiber fabric B to the refractory raw material A (refractory body), and more preferably exists (permeates) in the carbon fiber bundles b (gaps between the carbon fibers) to integrate the carbon fiber bundles b as a bundle, and therefore the adhesive c used in the preparation step (i) is desirably in a liquid state. From these conditions, the adhesive c to be attached to the carbon fiber fabric B in the preparation step (i) is preferably one or more selected from an organic resin solution, tar, pitch, organic glue, and inorganic sol (i.e., any one of these or a mixture of these).

[0022] Specific examples of adhesives C (tackifiers) include phenolic resins, epoxy resins, melamine resins, urea resins, alkyd resins, unsaturated polyester resins, polyurethane resins, thermosetting polyimide resins (resin solutions consisting of one or more of these organic resins), pitch, tar, starch paste, alumina sol, silica sol, zirconia sol, chromia sol, titania sol, magnesia sol, calcia sol, yttria sol, etc., and one or more selected from these can be used. In addition, these adhesives c can be thinned with a solvent to adjust the viscosity, but it is desirable to limit the use of solvents (e.g., water) that gasify even in the absence of oxygen at high temperatures of 500°C or higher to an amount equal to or less than the weight of the adhesive components.

[0023] Furthermore, when the adhesive c contains an organic substance such as an organic resin as an active ingredient, the organic substance preferably has a carbon residue rate of 6% by mass or more and 80% by mass or less. Here, the carbon residue rate of the adhesive c is measured based on the fixed carbon measurement method described in JIS K6910 (phenolic resin test method). When the refractory is used (when the actual machine is in operation), the temperature reaches 500°C or higher (measured at 900°C in JIS K6910) even inside. At this time, even in an environment with almost no oxygen inside, such as a graphite-containing refractory, if the active ingredient of the adhesive c is an organic substance such as an organic resin, a part of the adhesive c attached to the carbon fiber fabric B is gasified by decomposition or evaporation and dissipated outside the refractory. The carbon residue rate is thought to be an index of the weight ratio of the adhesive c that remains without being gasified and dissipated, and varies depending on the type and quality of the adhesive. In the present invention, the carbon residue rate of the adhesive c affects the fracture energy when a graphite-containing refractory using carbon fiber fabric B is exposed to high temperatures, which is an actual use environment, and an investigation was conducted. It was found that the fracture energy is likely to be high when an adhesive c (organic substance) with a carbon residue rate of 6 to 80% by mass is used. This is thought to be because the use of adhesive c (organic substance) with such a specific residual carbon ratio increases the adhesion between the refractory raw material A (refractory body) and the carbon fiber fabric B, making it easier to densify the refractory brick during molding. In addition, the amount of gas that escapes from the inside of the refractory when exposed to high temperatures can be suppressed, thereby suppressing the occurrence of cracks and increasing the fracture energy.

[0024] When the active ingredient of the adhesive c is an organic substance such as an organic resin, if the carbon content is less than 6% by mass, the amount of gas escaping from the inside of the refractory at high temperatures increases, and many defects such as pores are generated, making it difficult to increase the fracture energy. On the other hand, if the carbon content exceeds 80% by mass, almost no gas escapes from the inside of the refractory at high temperatures, and the refractory becomes too dense and brittle, making it difficult to increase the fracture energy. From the above viewpoints, the carbon content of the organic substance is preferably 20 to 80% by mass, and more preferably 40 to 80% by mass. Furthermore, in the present invention, it was found that high fracture energy can also be obtained when the active ingredient of adhesive c is inorganic fine particles such as alumina or silica (i.e., when adhesive c is an inorganic sol such as alumina sol or silica sol). This is thought to be because, even when inorganic fine particles (especially inorganic fine particles derived from inorganic sol) are used, the adhesion between the refractory raw material A (refractory body) and the carbon fiber fabric B is increased, making it easier for the refractory brick to become dense during molding, and in addition, when exposed to high temperatures during use, the inorganic fine particles derived from the inorganic sol are sintered, suppressing the occurrence of cracks and increasing the fracture energy.

[0025] In the preparation step (i), when the adhesive c is applied so as to cover the outer surface of the carbon fiber fabric B (carbon fiber bundles b) and the adhesive c is made to penetrate (impregnate) into the bundles of carbon fiber bundles b (gaps between the carbon fibers), for example, the carbon fiber fabric B is immersed in the adhesive c, which is a resin (resin solution) or an inorganic sol, or the adhesive c, which is a resin (resin solution) or an inorganic sol, is sprayed onto the carbon fiber fabric B. As another method, the adhesive c may be permeated (impregnated) into the bundle of carbon fiber bundles b in advance, and then the hardened or solidified carbon fiber fabric B may be prepared, and in the preparation step (i), the adhesive c may be adhered again to cover the outer surface of the carbon fiber fabric B.

[0026] In the molding step (ii), the carbon fiber fabric B to which the adhesive c has been attached in the preparation step (i) (preferably the carbon fiber fabric B to which the adhesive c has been attached on the outer surface and the adhesive c has been permeated (impregnated) into the bundles of carbon fiber bundles b) is embedded inside the refractory raw material A while the adhesive c is still viscous, and the refractory raw material A in which the carbon fiber fabric B has been embedded is molded to obtain a refractory molded body x (molded product of the refractory raw material). When molding is performed by press molding as shown in FIG. 1, a suitable amount of binder is usually added to the refractory raw material A and kneaded, and the carbon fiber fabric B to which the adhesive c has been attached as described above is embedded in the kneaded product, and then press molding is performed. As the binder, for example, phenol resin (main agent) + hexamine (hardening agent), carbon bond, ceramic bond, etc. are used. The refractory raw material A is a mixture of graphite (carbon raw material) and aggregate raw material, and its specific composition will be described in detail later.

[0027] Here, the adhesive c attached to the carbon fiber fabric B may be in a state in which it has a certain degree of hardening or solidification when the carbon fiber fabric B is embedded in the kneaded material, as long as it has an adhesiveness (so-called semi-dried state) that allows the carbon fiber fabric B and the refractory raw material A (kneaded material) to adhere or bond to each other, as described above. The carbon fiber fabric B embedded in the refractory raw material A is adhered or in close contact with the refractory raw material A via the adhesive c. When the carbon fiber fabric B is embedded in the refractory raw material A with the adhesive c attached to its outer surface and the adhesive c also permeating (impregnating) into the carbon fiber bundles b, the carbon fiber fabric B contains the adhesive c in the carbon fiber bundles b (i.e., the adhesive c is present in the gaps between the carbon fibers constituting the carbon fiber bundles b, thereby integrating the carbon fibers into a bundle), and the adhesive c is present between the carbon fiber fabric B and the refractory raw material A, so that the carbon fiber fabric B is adhered or in close contact with the refractory raw material A via the adhesive c.

[0028] Press molding is performed by filling a mold with the kneaded refractory raw material A and the carbon fiber fabric B, and as a method for filling the mold with the kneaded refractory raw material A together with the carbon fiber fabric B (carbon fiber fabric B with adhesive c attached; the same applies below), there is, for example, a method in which a certain amount of the kneaded material is charged into the mold, and then the carbon fiber fabric B is arranged (charged), and a certain amount of the kneaded material is again charged into the mold. Therefore, to produce a graphite-containing refractory in which multiple layers of carbon fiber fabric B are embedded inside the refractory raw material A as shown in Figure 2 using this method, a step of charging a certain amount of the kneaded material into the mold, and then arranging the carbon fiber fabric B on it, and a step of charging a certain amount of the kneaded material on it are repeatedly performed. Press molding can be performed using standard die press molding, which compresses in one direction within a die, but CIP molding can also be used, which applies pressure evenly from all directions using a liquid. For shapes where it is difficult to apply even pressure with unidirectional compression, such as shapes with different thicknesses in different parts, it is preferable to use CIP molding, as this reduces bias in the degree of compression depending on the part.

[0029] The molding step (ii) may be performed by a molding method other than press molding. Examples of molding methods other than press molding include molding by pouring, one of which is a method in which an inner frame is installed at the work site, which is the working surface of a pot or tundish, and an amorphous refractory (refractory raw material A) is poured into this inner frame, and the inner frame is removed after drying (drying step) and solidification. There is also a method in which the amorphous refractory (refractory raw material A) is poured into a formwork of a refractory shape instead of pouring into the work site, and the refractory is removed from the formwork after drying (drying step) and solidification, and then transported to the work site for construction. Although this method requires a lot of work to install the refractory at the work site, it is preferable because it is easy to embed the carbon fiber fabric B when pouring the amorphous refractory into the formwork and to control the temperature during solidification. In these casting methods, the carbon fiber fabric B is placed in the inner frame or mold, and then the unshaped refractory (the refractory raw material A) is poured into the inner frame or mold, and dried (drying process) and solidified. Therefore, the graphite-containing refractory produced by the present invention includes not only so-called refractory bricks produced through press molding, but also refractories which are molded by pouring into a working area, such as a working surface of a ladle or tundish, and then dried and solidified as is, as described above.

[0030] In the present invention, the refractory molded body x obtained in the molding step (ii) is carbon fiber bundles b constituting the carbon fiber fabric B in the same direction, the interval between adjacent carbon fiber bundles b is larger than the maximum particle size of the aggregate constituting the refractory raw material A, and in the cross section of the refractory molded body in the plane direction of the carbon fiber fabric B, the area ratio of the carbon fiber fabric B to the cross section of the refractory molded body is 20% or more. That is, the refractory raw material A and the carbon fiber fabric B are selected so as to satisfy this condition, and the molding step (ii) is carried out. Details of this condition will be described later.

[0031] Hereinafter, the configuration of the carbon fiber fabric B to be embedded in the refractory raw material A in the molding step (ii) and the conditions for embedding the carbon fiber fabric B in the refractory molded body x will be described. As shown in Fig. 3, the carbon fiber fabric B is a sheet-like member (woven fabric) formed by weaving carbon fiber bundles b in two or more directions (i.e., weaving while oriented in two or more directions). The number of orientations of the carbon fiber bundles b is arbitrary, but the carbon fiber fabric B of this embodiment is formed by weaving the carbon fiber bundles b while oriented in two perpendicular directions. Note that if the orientation direction of the carbon fiber bundles b is in one direction, a carbon fiber fabric cannot be formed, and therefore a graphite-containing refractory material with carbon fiber fabric embedded cannot be obtained. The carbon fiber fabric B is embedded (placed) inside the refractory raw material A (refractory molding x), and as shown in the "enlarged widthwise cross-sectional view of the carbon fiber bundle b" in Figure 3, in this embodiment, the carbon fiber bundle b contains an adhesive c, and is embedded (placed) in a state of being adhered or adhered to the refractory raw material A via the adhesive c.

[0032] The carbon fiber fabric B may be arranged in any manner within the refractory raw material A (refractory molded body x) without any particular limitation, but since the tensile stress that causes cracks during operation occurs in the longitudinal direction of the refractory, it is preferable to arrange (embed) the carbon fiber fabric B linearly along one direction, and particularly preferable to arrange (embed) the carbon fiber fabric B along a direction perpendicular to the refractory operating surface s1. The carbon fiber fabric B may be composed of two or more overlapping layers of fabric. The carbon fiber fabric B embedded inside the refractory raw material A (refractory molded body x) may or may not have its end exposed on the surface of the refractory molded body x. In the latter case, on the working surface s1 side of the refractory, it is preferable that the distance between the end of the carbon fiber fabric B and the working surface s1 is as small as possible, but on the counter working surface s2 side, the distance between the end of the carbon fiber fabric B and the counter working surface s2 may be relatively large. This is because the carbon fiber fabric B does not need to be embedded in the part on the counter working surface s2 side of the refractory that is expected to remain even after use is finished.

[0033] The carbon fiber bundles b in the same direction (carbon fiber bundles b woven in the same direction) that make up the carbon fiber fabric B are woven so that the interval L (L1, L2 in Fig. 3) between adjacent carbon fiber bundles b is larger than the maximum grain size of the aggregate that makes up the refractory raw material A. By making the interval L (L1, L2) between the carbon fiber bundles b larger than the maximum grain size of the aggregate raw material in this way, the entanglement between the carbon fiber fabric B and the aggregate raw material can be improved, and high fracture energy can be maintained without causing lamination during molding. Here, the interval L between the carbon fiber bundles b is the distance between the outer surfaces of the carbon fiber bundles b, as shown as L1 and L2 in Fig. 3. In addition, the distance L between adjacent carbon fiber bundles b (L1, L2 in FIG. 3) is preferably more than 3 mm. This allows the carbon fiber fabric B to be well entangled with not only the coarse particles but also the fine particles as described above, and also makes it difficult for peeling caused by the carbon fiber bundles, known as lamination, to occur during molding. There is no particular upper limit to this distance L (L1, L2 in FIG. 3), but in view of the relationship with the density of carbon fibers described below, it is generally preferable to set the upper limit at about 50 mm.

[0034] The carbon fiber fabric B is embedded (placed) inside the refractory raw material A (refractory molding x) so that the area ratio of the carbon fiber fabric B to the cross-sectional area of ​​the refractory molding in the cross-section in the plane direction is 20% or more. Here, the area of ​​the carbon fiber fabric B is the area calculated by w1×w2 shown in FIG. 3. By setting the area ratio of the carbon fiber fabric B to the cross-sectional area of ​​the refractory molding to 20% or more in this way, the fracture energy is increased and crack extension can be appropriately suppressed. From this viewpoint, it is more preferable that the area ratio of the carbon fiber fabric B to the cross-sectional area of ​​the refractory molding is 40% or more.

[0035] If the thickness of the carbon fiber fabric B is too small, the fracture energy is unlikely to increase, and the crack propagation suppression effect is relatively low. On the other hand, if the thickness is too large, the carbon fiber bundles b constituting the carbon fiber fabric B are likely to spring back (rebound after compression) during molding. For this reason, the thickness of the carbon fiber fabric B is preferably 0.1 mm or more and 3 mm or less. Also, as in this embodiment, it is preferable that the carbon fiber fabric B is embedded (arranged) in two or more layers at intervals in the thickness direction according to the thickness of the refractory molding x. Usually, in this case, two or more layers of the carbon fiber fabric B are embedded in parallel at intervals. In this way, by embedding multiple layers of the carbon fiber fabric B according to the thickness of the refractory molding x, the effect of suppressing crack extension due to an increase in fracture energy can be more appropriately obtained. In addition, when two or more layers of carbon fiber fabric B are embedded in parallel with a gap therebetween, if the gap between adjacent carbon fiber fabrics B is too small, springback is likely to occur during molding, so the gap between adjacent carbon fiber fabrics B is preferably 10 mm or more. Here, the gap between adjacent carbon fiber fabrics B refers to the distance between the outer surfaces of the carbon fiber fabrics B.

[0036] The carbon fiber bundles b constituting the carbon fiber fabric B preferably have a width w of more than 1 mm and not more than 15 mm. Here, the width w of the carbon fiber bundles b refers to the length of the long side or major axis in the cross section of the carbon fiber bundles b in the width direction, as shown in FIG. 3 (however, when the cross section in the width direction is a square or a circle, the length of one side or the diameter). Since the width w of the carbon fiber bundles b is more than 1 mm, the number of carbon fiber bundles b woven together can be reduced when the same number of carbon fibers are used, so that the bulkiness of the carbon fiber fabric B caused by the woven carbon fiber bundles b can be suppressed, and the tensile strength unique to the carbon fiber fabric can be utilized. On the other hand, since the width w of the carbon fiber bundles b is 15 mm or less, it is possible to reduce interference between the coarse grain material of the raw material A used for the refractory material and the carbon fiber bundles b, or to reduce the melting damage of the carbon fiber bundles b themselves from triggering the melting damage of the refractory.

[0037] The carbon fiber fabric used in the present invention is a woven carbon fiber bundle made by bundling carbon fibers. 2 The carbon fiber bundle has a mass per bundle (however, when the carbon fiber fabric is composed of two or more overlapping layers of fabric, the total mass of the overlapping layers of fabric) of about 40 to 1,300 g, a fiber diameter of about 1 to 45 μm, and about 1,000 to 300,000 carbon fibers per bundle. If the number of carbon fibers (existence density) arranged in the refractory raw material A is too small, the contact area between the refractory raw material and the carbon fiber bundle becomes small, and the effect of the present invention relatively decreases, whereas if the number of carbon fibers (existence density) is too large, the carbon fiber bundle is likely to spring back during molding, so that it is preferable that the number of carbon fibers (existence density) arranged in the refractory raw material A is within an appropriate range. Specifically, the carbon fiber fabric B usually has a density (embedding density) of carbon fibers constituting the carbon fiber fabric B in a cross section of the refractory molded body in a direction perpendicular to the plane direction of the carbon fiber fabric B (usually, a cross section of the refractory molded body parallel to the working surface s1 of the refractory) of 10 to 2000 fibers / mm 2 It is preferable that the refractory raw material A (the refractory molded body x) is embedded therein so that the refractory raw material A is approximately equal to the refractory raw material A.

[0038] As described above, in the present invention, the carbon fiber fabric B embedded (placed) inside the refractory raw material A (refractory molding x) must have a distance between adjacent carbon fiber bundles b larger than the maximum particle size of the aggregate constituting the refractory raw material A, and the area ratio of the carbon fiber fabric B to the cross-sectional area of ​​the refractory molding in the cross-section of the refractory molding in the plane direction of the carbon fiber fabric B must be 20% or more. Furthermore, by satisfying the following conditions: (i) the thickness of the carbon fiber fabric B is 0.1 mm or more and 3 mm or less, and (ii) the width of the carbon fiber bundles b constituting the carbon fiber fabric B is more than 1 mm and 15 mm or less, the adhesion between the refractory raw material A and the carbon fiber fabric B is further increased, so that the refractory (brick) is easily densified during molding, and the fracture energy is significantly increased. In addition, the amount of gas escaping from the inside of the refractory when exposed to high temperatures is suppressed, thereby suppressing the occurrence of cracks.

[0039] The refractory molded body x obtained in the molding step (ii) may be used as a product as it is, but is usually dried in a drying step (iii). This drying step (iii) is usually carried out at about 200 to 230° C. for the purpose of drying (curing) the refractory molded body x. In addition, the refractory molded body x obtained by the above-mentioned casting is dried and solidified by heating the refractory molded body x held in an inner frame installed at the construction site or in a form installed at another location with a heating means such as a heating burner. After that, the inner frame is removed and the mold is taken out.

[0040] As a result of the above, a graphite-containing refractory is obtained in which the carbon fiber fabric B is embedded inside the refractory raw material A (refractory body) and this carbon fiber fabric B is adhered or adhered to the refractory raw material A (refractory body) via the adhesive c (preferably, the adhesive c further penetrates into the carbon fiber bundles b of the carbon fiber fabric B, so that the adhesive c exists within the carbon fiber bundles b and the carbon fiber bundles b are integrated into a bundle by the adhesive c). The graphite-containing refractory produced by the method of the present invention can be used as a refractory for various facilities and containers, and is particularly suitable as a refractory lining for refining vessels and transport vessels used in steelworks, such as converters, molten iron pretreatment vessels (blast furnace ladles, torpedoes, etc.), ladles, etc. In particular, it is suitable as a refractory lining for converters, which are used in extremely severe environments, and among these, it is particularly suitable as a tuyere brick for forming the tuyere portion.

[0041] Next, the composition of the refractory raw material A will be described. The refractory raw material A preferably contains 1% by mass or more and 80% by mass or less of the graphite raw material. By making the content of the graphite raw material 1% by mass or more, the crack resistance of the graphite-containing refractory can be ensured, and the oxidative loss of the carbon fibers inside the refractory can be suppressed. On the other hand, by making the content of the graphite raw material 80% by mass or less, the oxidative loss of the graphite raw material on the surface of the refractory can be suppressed. As the graphite (carbon raw material), scaly graphite or the like is generally used. As such, refractories in which the refractory raw material A contains 1 to 80% by mass of the graphite raw material include, for example, magnesia-carbon refractories (graphite-containing refractories with magnesia raw material as aggregate), which are refractories mainly composed of magnesia and carbon, alumina-silicon carbide-silica-carbon refractories (graphite-containing refractories with alumina raw material, silicon carbide raw material, and silica raw material as aggregate), which are refractories mainly composed of alumina, silicon carbide, silica, and carbon, and alumina, carbon. Examples include alumina-silicon carbide-carbon refractories (graphite-containing refractories with alumina raw materials and silicon carbide raw materials as aggregate), which are refractories whose main components are silicon carbide and carbon; silica-silicon carbide-carbon refractories (graphite-containing refractories with silica raw materials and silicon carbide raw materials as aggregate), which are refractories whose main components are silica, silicon carbide and carbon; and alumina-silicon carbide-silica-carbon refractories that use refractory scrap as part of the aggregate raw material.

[0042] In general, the lining (including the tuyere) of the converter used in the refining process is made of magnesia-carbonaceous refractories (graphite-containing refractories with magnesia raw materials as aggregate), which are refractories mainly composed of magnesia and carbon. When the refractory raw material A is a magnesia-carbonaceous refractory raw material, it is preferable that the refractory raw material A contains 20% to 99% by mass of magnesia raw materials, which suppresses cracking due to thermal spalling and provides a refractory with corrosion resistance that can withstand the erosion of converter slag containing a large amount of FeO. It is preferable to use a high-purity magnesia raw material with a magnesia concentration of 90% by mass or more as the magnesia raw material.

[0043] Generally, the lining of the molten iron pretreatment vessels (torpedoes, blast furnace ladles, etc.) used in the molten iron pretreatment process is made of refractories whose main components are alumina, silicon carbide and carbon, such as alumina-silicon carbide-carbon refractories (graphite-containing refractories with alumina raw materials and silicon carbide raw materials as aggregates) or alumina-silicon carbide-silica-carbon refractories (graphite-containing refractories with alumina raw materials, silicon carbide raw materials and silica raw materials as aggregates), whose main components are alumina, silicon carbide, silica and carbon. When the refractory raw material A is an alumina-silicon carbide-carbonaceous refractory raw material or an alumina-silicon carbide-silica-carbonaceous refractory raw material, it is preferable that the alumina raw material contains 10% by mass or more and 95% by mass or less of the alumina raw material, which provides high corrosion resistance against the molten iron pretreatment slag and further suppresses the occurrence of cracks due to thermal spalling. Note that it is preferable to use a high-purity alumina raw material with an alumina concentration of 70% by mass or more as the alumina raw material.

[0044] Furthermore, when the refractory raw material A is an alumina-silicon carbide-carbonaceous refractory raw material or an alumina-silicon carbide-silica-carbonaceous refractory raw material, it is preferable that the refractory raw material A contains 1 mass% or more of silicon carbide raw material. By containing 1 mass% or more of silicon carbide raw material, oxidation of graphite in an air atmosphere can be suppressed, so that high crack resistance can be maintained. In addition, it is preferable to use a high-purity silicon carbide raw material having a silicon carbide concentration of 80 mass% or more as the silicon carbide raw material. Furthermore, when the refractory raw material A is an alumina / silicon carbide / silica / carbonaceous refractory raw material, it is preferable that the silica raw material is contained in an amount of 1 mass % or more and 50 mass % or less, which makes it possible to achieve both high cracking resistance and high resistance to corrosion.

[0045] The magnesia-carbon refractories used for lining the converter are used under very severe conditions, such as mechanical impacts from the charge, abrasion due to stirring of molten steel and molten slag, slag erosion by molten slag, and sudden temperature changes during converter operation. For this reason, it is preferable to use magnesia-carbon refractories with high durability that can withstand the severe conditions in order to ensure stable operation. Similarly, alumina-silicon carbide-carbon refractories and alumina-silicon carbide-silica-carbon refractories used for lining the molten pig iron pretreatment vessels such as torpedoes and blast furnace ladles are also used under very severe conditions, so it is preferable to use refractories that can withstand these conditions. According to the present invention, the fracture energy of the graphite-containing refractories used under these very severe conditions is significantly improved compared to conventional graphite-containing refractories, and high durability is obtained.

[0046] In addition, when the refractory raw material A is a silica-silicon carbide-carbonaceous refractory raw material that is a refractory raw material mainly composed of silica, silicon carbide, and carbon, it is preferable to contain 1 mass% or more of silicon carbide raw material and 1 mass% to 50 mass% of silica raw material, which allows both high cracking resistance and high resistance to melting damage to be achieved. By containing 1 mass% or more of silicon carbide raw material, oxidation of graphite in the air atmosphere can be suppressed, so high cracking resistance can be maintained. In addition, it is preferable to use a high-purity silicon carbide raw material with a silicon carbide concentration of 80 mass% or more as the silicon carbide raw material.

[0047] Here, as the alumina raw material, for example, one or more of alumina shale, white alumina, brown alumina, etc. are used. As the silicon carbide raw material, for example, one or more of green silicon carbide, black silicon carbide, etc. are used. As the silica raw material, for example, one or more of aloesite, mullite, etc. are used. The graphite-containing refractory can further contain (mix) a metal powder raw material for the purpose of suppressing the amount of heat radiation from the steelmaking vessel while increasing durability. Examples of the metal powder raw material include metal Si, metal Al, metal Al-Si, Al4SiC4, and B4C, and one or more of these can be contained. The content of the metal powder raw material is not particularly specified, but is usually preferably about 1 to 5 mass%. If the content (mixture amount) of the metal powder raw material is less than 1 mass%, the effect of improving durability by mixing the metal powder raw material cannot be sufficiently obtained, while if it exceeds 5 mass%, the strength becomes too high, so that cracks are likely to occur when used in an actual machine, making the bricks more likely to break, and the number of times it can be used in an actual machine may decrease.

[0048] The refractory raw material A may contain 10% by mass or more and 90% by mass or less of refractory chips obtained by crushing used refractories as aggregate raw materials. In particular, when the refractory raw material A is an alumina-silicon carbide-carbonaceous refractory raw material (including alumina-silicon carbide-silica-carbonaceous refractory raw material that further contains a silica raw material; the same applies below), the refractory chips obtained by crushing used alumina-silicon carbide-carbonaceous refractories (including alumina-silicon carbide-silica-carbonaceous refractories that further contain a silica raw material; the same applies below) can be suitably used as the aggregate raw material. When refractory waste is contained in this manner, the remainder of the refractory raw material A is unused raw material (virgin raw material).

[0049] In the refractory raw material A consisting of alumina, silicon carbide, and carbonaceous refractories, when the content of refractory waste obtained by crushing used alumina, silicon carbide, and carbonaceous refractories is 10% by mass or more and 90% by mass or less, the cracking resistance and corrosion resistance are comparable to those of a graphite-containing refractory made only from virgin raw materials. The reason for this is that although the purity of the refractory waste raw material is lower than that of the virgin raw material, the combination of the refractory waste raw material and the virgin raw material can suppress a significant decrease in the corrosion resistance of the Al2O3 component in the refractory waste raw material. However, when the content of the refractory waste is more than 90% by mass, the content of the virgin raw material is too low, so a significant decrease in the corrosion resistance of the Al2O3 component in the refractory waste raw material cannot be suppressed. In addition, when the content of the refractory waste is less than 10% by mass, the reuse rate of the refractory waste is too low, so the cost of treating the refractory waste as industrial waste increases significantly. EXAMPLES

[0050] In order to study the blending of magnesia-carbonaceous raw materials for magnesia-carbonaceous refractories (graphite-containing refractories with magnesia raw materials as aggregate) used in converters, refractory molded products were produced using magnesia raw materials as aggregate with the raw material blend shown in Table 1, i.e., graphite-containing refractories without embedded carbon fiber fabric. When kneading and molding the refractory raw materials, 3 mass% of phenolic resin and 0.3 mass% of hexamine were blended as binders on an outer basis of the refractory raw materials. The melting wear resistance and cracking resistance of the graphite-containing refractories produced were evaluated using the following methods. The results are also shown in Table 1.

[0051] The corrosion resistance was evaluated based on the amount of corrosion measured by the lining method using a high-frequency induction furnace as shown in FIG. 6 (Test Method). In the test using the lining method, the test temperature was 1650°C, the temperature was held for 4 hours, and synthetic slag having the composition shown in Table 2 was added every hour. After cooling, the amount of corrosion on the working surface was measured. From the amount of corrosion, a corrosion index was calculated with the amount of corrosion of Blending Example 1-4 in Table 1 set to 100. FIG. 6(A) is an explanatory diagram showing the test implementation status in a vertical cross section of the test furnace and the cylindrical sample, FIG. 6(B) is a plan view of the cylindrical sample shown in FIG. 6(A), and FIG. 6(C) is a perspective view showing one of the test pieces constituting the cylindrical sample shown in FIG. 6(A) and (B). For crack resistance, the dynamic modulus of elasticity E0 in the longitudinal direction of a 150 mm x 150 mm x 300 mm sample was measured in accordance with the ultrasonic pulse method specified in JIS R1605, and then a cycle of heating at 1500°C for 10 minutes, water cooling for 5 minutes, and air cooling for 10 minutes was repeated three times. After these three cycles were completed, the dynamic modulus of elasticity E3 was measured again using the above method, and the rate of change in the dynamic modulus of elasticity E3 / E0 before and after the test was used as an index for evaluation.

[0052] As shown in the blending examples 1-2 to 1-8 in Table 1, when the graphite content is 1% by mass or more and 80% by mass or less, and the magnesia raw material content is 20% by mass or more and 99% by mass or less, the corrosion resistance and cracking resistance are almost constant. However, as shown in the blending example 1-1, when the graphite content is less than 1% by mass, the corrosion resistance is significantly reduced. Also, as shown in the blending example 1-9, when the magnesia raw material content is less than 20% by mass, the corrosion resistance is significantly reduced. From these, it can be seen that in order to ensure the cracking resistance of the graphite-containing refractory, it is preferable to set the graphite content to 1% by mass or more, and further, in order to achieve both corrosion resistance and cracking resistance in the blending of the magnesia-carbonaceous raw material, it is preferable to set the graphite content to 1% by mass or more and 80% by mass or less, and the magnesia raw material content to 20% by mass or more and 99% by mass or less.

[0053] The graphite-containing refractories of the invention and comparative examples, in which the carbon fiber fabric B was embedded (disposed) inside the refractory body, were manufactured by the procedure shown in FIG. 1. In this case, the carbon fiber fabric B was immersed in a phenolic resin (resin solution) as an adhesive c in advance, and the carbon fiber fabric B, in which the phenolic resin (sap solution) had permeated and adhered to the inside and outside of the carbon fiber bundles b, was embedded in the refractory raw material A. In the graphite-containing refractory manufactured in this way, the carbon fiber fabric B was embedded (in the case of multiple layers of the carbon fiber fabric B, the carbon fiber fabric B was embedded in parallel at equal intervals) along the longitudinal direction of the refractory body (refractory molded body x) as shown in FIG. 2, and the carbon fiber fabric B contains the adhesive c in the bundles of carbon fiber bundles b constituting the carbon fiber fabric B, and is bonded or adhered to the refractory raw material A via the adhesive c. When the refractory raw material A was kneaded and molded, 3 mass % of phenolic resin and 0.3 mass % of hexamine were mixed as binders on the outer side of the refractory raw material A. The produced graphite-containing refractories were evaluated for bending strength, fracture energy, resistance to melting damage, and resistance to cracking by the following methods.

[0054] As shown in Fig. 4 (Test Method), bending strength was measured using a test piece (test piece size: 150mm x 150mm x 300mm) in which carbon fiber fabric was embedded inside the refractory body along its longitudinal direction (if there were multiple layers of carbon fiber fabric, they were embedded in parallel at equal intervals), with a center distance of 100mm and a load application rate of 0.5mm / min, in accordance with the three-point bending test method described in JIS R2213. Note that Fig. 4(A) is an explanatory diagram that shows a schematic diagram of the implementation of the three-point bending strength test, and Fig. 4(B) is an explanatory diagram that shows a schematic diagram of the end face of the test piece in Fig. 4(A). As shown in Fig. 5, the fracture energy was calculated based on the position where the first peak value was shown in the load-displacement curve obtained from the three-point bending strength test, and the area within a range of 1 mm of displacement from the reference position.

[0055] The cracking resistance and corrosion resistance were evaluated by the above-mentioned method, and the test piece for evaluating the cracking resistance was one in which the carbon fiber fabric was embedded inside the refractory body along its longitudinal direction (if the carbon fiber fabric was multiple layers, it was embedded in parallel at equal intervals).The test piece for evaluating the corrosion resistance was one in which the carbon fiber fabric was embedded perpendicularly to the surface (working surface s1 of the refractory) that comes into contact with slag or molten steel (if the carbon fiber fabric was multiple layers, it was embedded in parallel at equal intervals). Regarding the overall evaluation of the properties of refractory bricks, the fracture energy is 15 kJ / m 2 If the crack resistance is 0.50E3 / E0 or more, it is rated as "Excellent" (rating: ◎), and if the fracture energy is 10kJ / m 2 More than 15kJ / m 2 less than 0.40E3 / E0, and crack resistance between 0.40E3 / E0 and 0.50E3 / E0 is "good" (evaluation: ◯). Fracture energy is 10kJ / m 2 When the crack resistance was less than 0.40E3 / E0, or when the carbon fiber fabric could not be formed, the rating was "poor" (rating x).

[0056] Tables 3 to 9 show the structures and properties (flexural strength, fracture energy, melting resistance, and cracking resistance) of the carbon fiber-containing magnesia-carbonaceous bricks (graphite-containing refractories in which carbon fiber fabric is embedded inside the refractory body) of the invention examples and comparative examples. Note that the terms "refractory cross section" and "refractory cross-sectional area" in the following explanation and in Tables 3 to 17 respectively mean the "refractory cross section" and "refractory cross-sectional area" of the refractory molding x. In these examples, the refractory body had the composition of Blending Example 1-4 in Table 1, and the maximum particle size of the aggregate (magnesia raw material) constituting the refractory body A was 3 mm. First, the examples in Table 3 examine the effects of the number of orientation directions of the carbon fiber bundles constituting the carbon fiber fabric (the number of directions in which the carbon fiber bundles are woven) and the area ratio of the carbon fiber fabric to the cross-sectional area of ​​the refractory (the area ratio of the carbon fiber fabric to the cross-sectional area of ​​the refractory in the cross-section of the refractory in the plane direction of the carbon fiber fabric) embedded inside the refractory body on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks.

[0057] As shown in Examples 1-1 to 1-5, when the area ratio of the carbon fiber fabric to the cross-sectional area of ​​the refractory was 20% or more, the characteristics of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent" or "good." On the other hand, as shown in Comparative Example 1-1, when the occupied area ratio of the carbon fiber fabric to the cross-sectional area of ​​the refractory was less than 20%, the properties of the carbon fiber-containing magnesia-carbonaceous brick were evaluated as "poor." Furthermore, as shown in Comparative Example 1-2, when the carbon fiber bundles were oriented in only one direction, a carbon fiber fabric could not be formed, and therefore a brick with an embedded carbon fiber fabric could not be manufactured. From these findings, it was found that the fracture energy and crack resistance of the carbon fiber-containing magnesia-carbonaceous brick can be increased by embedding a carbon fiber fabric in which carbon fiber bundles are woven in two or more directions in the refractory body and setting the area ratio of the carbon fiber fabric to the cross-sectional area of ​​the refractory to 20% or more. It was also found that the fracture energy and crack resistance of the carbon fiber-containing magnesia-carbonaceous brick can be increased even more by setting the area ratio of the carbon fiber fabric to the cross-sectional area of ​​the refractory to 40% or more.

[0058] The examples in Table 4 examine the effect of the thickness of the carbon fiber fabric embedded inside the refractory body on the bending strength, fracture energy, and crack resistance of the carbon fiber-containing magnesia-carbonaceous brick. As shown in Examples 1-3 and 2-2 to 2-4, when the thickness of the carbon fiber fabric was 0.1 mm or more and 3 mm or less, the characteristics of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent." On the other hand, as shown by Examples 2-1 and 2-5, when the thickness of the carbon fiber fabric was less than 0.1 mm or more than 3 mm, the properties of the carbon fiber-containing magnesia-carbon bricks were slightly inferior to those of Examples 1-3 and 2-2 to 2-4. From the above, it was found that if the thickness of the carbon fiber fabric is between 0.1 mm and 3 mm, the fracture energy and crack resistance of the carbon fiber-containing magnesia-carbon brick can be maintained at a particularly high level.

[0059] The examples in Table 5 examine the effect of the carbon fiber bundle width w on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks for carbon fiber woven fabrics embedded inside the refractory body. As shown in Examples 1-3 and 3-2 to 3-5, when the width w of the carbon fiber bundle was more than 1 mm and not more than 15 mm, the properties of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent." On the other hand, as shown in Example 3-1, when the width w of the carbon fiber bundle was 1 mm, the properties of the magnesia-carbon brick containing carbon fiber were slightly deteriorated. Also, as shown in Example 3-6, when the width w of the carbon fiber bundle was more than 15 mm, the properties of the magnesia-carbon brick containing carbon fiber were slightly deteriorated.

[0060] The examples in Table 6 examine the effect of the number of layers of carbon fiber fabric embedded inside the refractory body (number of embedded layers) on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks. As shown in Examples 1-3 and 5-2 to 5-4, when the number of embedded layers of carbon fiber fabric was two or more, the characteristics of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent." On the other hand, as shown in Example 5-1, when the number of embedded layers of carbon fiber fabric was one, the characteristics of the carbon fiber-containing magnesia-carbon brick were evaluated as "good." From the above, it was found that the magnesia-carbon brick containing carbon fiber exhibits excellent properties when the number of embedded layers of carbon fiber fabric is one, and that it exhibits even better properties when two or more layers are embedded.

[0061] The examples in Table 7 examine the effect of the embedding spacing (spacing between adjacent carbon fiber fabrics) of two or more layers of carbon fiber fabric embedded inside the refractory body on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks. As shown in Examples 1-3 and 6-2 to 6-5, when the embedding interval of the carbon fiber fabric was 10 mm or more, the properties of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "excellent." On the other hand, as shown in Example 6-1, when the embedding interval of the carbon fiber fabric was less than 10 mm, the properties of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "good." From the above, it was found that the magnesia-carbon brick containing carbon fiber exhibits particularly excellent properties when the carbon fiber fabric is embedded at intervals of 10 mm or more.

[0062] The examples in Table 8 are for carbon fiber fabrics embedded inside the refractory body, and are carbon fiber bundles woven in the same direction. The effects of the spacing L between adjacent carbon fiber bundles on the bending strength, fracture energy and crack resistance of the carbon fiber-containing magnesia-carbonaceous bricks were investigated. As shown in Examples 1-3 and 7-1, when the interval L between adjacent carbon fiber bundles is greater than the maximum particle size (3 mm) of the aggregate constituting the refractory raw material, the properties of the carbon fiber-containing magnesia-carbonaceous brick are evaluated as "excellent." On the other hand, as shown in Comparative Example 7-1, when the interval L between adjacent carbon fiber bundles is equal to or less than the maximum particle size (3 mm) of the aggregate constituting the refractory raw material, the properties of the carbon fiber-containing magnesia-carbonaceous brick are evaluated as "poor." Note that Examples 1-3 and 7-1 also satisfy the preferred condition of the present invention that "the interval L between adjacent carbon fiber bundles is greater than 3 mm." From the above, it was found that when the distance L between adjacent carbon fiber bundles in the carbon fiber fabric is made larger than the maximum particle size of the aggregate that constitutes the refractory raw material, the carbon fiber-containing magnesia-carbon brick exhibits particularly excellent properties.

[0063] The examples in Table 9 examine the effect of the residual carbon ratio of the adhesive component (phenolic resin) contained in the carbon fiber bundles that make up the carbon fiber fabric and that bonds or adheres the carbon fiber fabric to the refractory body on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks. As shown in Examples 1-3, 8-2 and 8-3, when the carbon residual rate of the adhesive component was between 6% and 80%, the characteristics of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "excellent". On the other hand, as shown in Example 8-1, when the carbon residual rate of the adhesive component was less than 6%, the characteristics of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "good". Also, as shown in Example 8-4, when the carbon residual rate of the adhesive component was more than 80%, the characteristics of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "good". From the above, it was found that when an organic substance is used as an adhesive component that is contained within the carbon fiber bundles of a carbon fiber fabric and that bonds or adheres the carbon fiber fabric to the refractory body, if an adhesive component with a residual carbon rate of 6% or more and 80% or less is used, the carbon fiber-containing magnesia-carbon brick will exhibit particularly excellent properties.

[0064] A similar study was also conducted on carbon fiber- and graphite-containing refractories (refractory bricks) made of alumina raw materials, silicon carbide raw materials, and silica raw materials as aggregates, which are used for linings of molten iron pretreatment vessels, etc. The examples in Table 10 examine the effects of the composition of carbon fiber-containing alumina-silica-silicon carbide-carbonaceous bricks (graphite-containing refractories made of alumina raw materials, silicon carbide raw materials, and silica raw materials as aggregates) used for the lining of molten iron pretreatment vessels on the bending strength, fracture energy, crack resistance, and corrosion resistance of the graphite-containing refractories. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside an alumina-silica-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregates (alumina raw material, silicon carbide raw material, silica raw material) constituting the refractory body was set to 3 mm.

[0065] As shown by Examples 9-2 to 9-8, when the content of alumina raw material was 10% by mass or more and 95% by mass or less, the content of silica raw material was 1% by mass or more and 50% by mass or less, the content of silicon carbide raw material was 1% by mass or more, and the content of graphite was 1% by mass or more and 80% by mass or less, the fracture energy was high and both high cracking resistance and high corrosion resistance were achieved. On the other hand, as shown in Example 9-1, when the alumina raw material content is less than 10 mass%, the silica raw material content is less than 1 mass%, the silicon carbide raw material content is less than 1 mass%, and the graphite content is more than 80 mass%, the fracture energy, crack resistance, and corrosion resistance are all decreased.

[0066] Furthermore, as shown in Example 9-9, when the alumina raw material content exceeds 95 mass%, the silica raw material content is less than 1 mass%, the silicon carbide raw material content is less than 1 mass%, and the graphite content is less than 1 mass%, the generation of cracks due to thermal spalling cannot be suppressed, and the fracture energy and crack resistance are reduced. From the above, it was found that in carbon fiber-containing alumina-silica-silicon carbide-carbonaceous refractories, high corrosion resistance and high fracture energy / crack resistance can be achieved simultaneously if the alumina raw material content is between 10% and 95% by mass, the silica raw material content is between 1% and 50% by mass, the silicon carbide raw material content is 1% by mass or more, and the graphite content is between 1% and 80% by mass.

[0067] The examples in Table 11 are alumina-silica-silicon carbide-carbonaceous bricks containing carbon fiber (graphite-containing refractories using alumina raw materials, silicon carbide raw materials, and silica raw materials as aggregates) used for the lining of molten iron pretreatment vessels. For graphite-containing refractories using refractory scrap obtained by crushing used alumina-silica-silicon carbide-carbonaceous refractories as part of the aggregate raw materials, the effects of the refractory scrap content on the bending strength, fracture energy, cracking resistance, and corrosion resistance of the graphite-containing refractories were investigated. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside an alumina-silica-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregates (alumina raw material, silicon carbide raw material, silica raw material) constituting the refractory body was set to 3 mm.

[0068] As shown in Examples 10-1 to 10-3, when the content of refractory scrap is 10% by mass or more and 90% by mass or less, the fracture energy, crack resistance, and corrosion resistance are comparable to those of the graphite-containing refractory material using only virgin raw materials shown in Table 10. On the other hand, as shown in Example 10-4, when the content of refractory scrap exceeded 90 mass %, the fracture energy, crack resistance, and corrosion resistance decreased. From the above, it was found that for carbon fiber-containing graphite-containing refractories made from refractory scrap obtained by crushing used alumina, silica, silicon carbide, and carbonaceous refractory scrap as the aggregate raw material, if the refractory scrap content is between 10% and 90% by mass, the fracture energy can be maintained high and, further, the graphite-containing refractories have the same level of cracking resistance and corrosion resistance as those made from graphite-containing refractories made only from virgin raw materials.

[0069] The examples in Table 12 examine the effects of the composition of carbon fiber-containing alumina / silicon carbide / carbonaceous bricks (graphite-containing refractories using alumina raw materials and silicon carbide raw materials as aggregates) on the bending strength, fracture energy, crack resistance, and corrosion resistance of the graphite-containing refractories. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside an alumina-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregate (alumina raw material, silicon carbide raw material) constituting the refractory body was set to 3 mm.

[0070] As shown in Examples 11-2 to 11-4, when the content of the alumina raw material is from 10% by mass to 95% by mass and the content of graphite is from 1% by mass to 80% by mass, high bending strength, fracture energy, crack resistance, and corrosion resistance are obtained. On the other hand, as shown in Example 11-1, when the alumina raw material content is less than 10 mass% and the graphite content is more than 80 mass%, the fracture energy, crack resistance, and corrosion resistance are decreased. Also, as shown in Example 11-5, when the alumina raw material content is more than 95 mass% and the graphite content is less than 1 mass%, the fracture energy and crack resistance are decreased. From the above, it was found that in carbon fiber-containing alumina / silicon carbide / carbonaceous refractories, if the alumina raw material content is between 10% and 95% by mass, and the graphite content is between 1% and 80% by mass, then high fracture energy, crack resistance, and corrosion resistance can be obtained.

[0071] The examples in Table 13 examine the effects of the composition of carbon fiber-containing silica / silicon carbide / carbonaceous bricks (graphite-containing refractories using silica raw material and silicon carbide raw material as aggregates) on the bending strength, fracture energy / crack resistance, and corrosion resistance of the graphite-containing refractories. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside a silica-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregate (silica raw material, silicon carbide raw material) constituting the refractory body was set to 3 mm.

[0072] As shown by Examples 12-2 to 12-4, when the content of the silica raw material was 1 mass % or more and 50 mass % or less, high bending strength, fracture energy, crack resistance, and corrosion resistance were obtained. On the other hand, as shown in Example 12-1, when the content of the silica raw material is less than 1 mass %, the fracture energy and crack resistance decrease. Furthermore, as shown in Example 12-5, when the content of the silica raw material exceeds 50 mass %, the generation of cracks due to thermal spalling cannot be suppressed, and the fracture energy and crack resistance decrease. From the above, it was found that in carbon fiber-containing silica / silicon carbide / carbonaceous refractories, if the content of silica raw material is between 1% by mass and 50% by mass, high bending strength, fracture energy, crack resistance, and corrosion resistance can be obtained.

[0073] Table 14 shows the results of evaluating the wear rate of the brick of the present invention in Example 1-3 (graphite-containing refractory material with magnesia raw material as aggregate) and a conventional brick with no embedded carbon fiber fabric installed in the tuyere of a converter. The conventional brick has the same composition and is manufactured by the same method as the brick of the present invention in Example 1-3, except that no embedded carbon fiber fabric is installed. As shown in Table 14, the wear rate of the brick of the present invention was reduced by 50% or more compared to the conventional brick. Table 15 shows the results of evaluating the wear rate of the brick of the present invention in Example 1-3 (graphite-containing refractory material with magnesia raw material as aggregate) and a conventional brick with no embedded carbon fiber fabric installed on the side wall of a ladle slag line. The conventional brick has the same composition and is manufactured by the same method as the brick of the present invention in Example 1-3, except that no embedded carbon fiber fabric is installed. As shown in Table 15, the wear rate of the brick of the present invention was reduced by 50% or more compared to that of the conventional brick.

[0074] Table 16 shows the results of evaluating the wear rate of the inventive brick of Example 9-5 (graphite-containing refractory material with aggregates of alumina raw materials, silicon carbide raw materials, and silica raw materials) and a conventional brick with no embedded carbon fiber fabric, which were installed on the side wall of a blast furnace ladle, a vessel for pre-treating molten iron. The conventional brick had the same composition and was manufactured by the same method as the inventive brick of Example 9-5, except that no embedded carbon fiber fabric was used. As shown in Table 16, the wear rate of the inventive brick was reduced by about 20% to 30% compared to the conventional brick. As shown in Tables 14 to 16, it was found that when the brick of the present invention is applied to a converter, a ladle, or a molten iron pretreatment vessel, the wear rate of the actual equipment can be significantly reduced.

[0075] [Table 1]

[0076] [Table 2]

[0077] [Table 3]

[0078] [Table 4]

[0079] [Table 5]

[0080]

Table 6

[0081]

Table 7

[0082]

Table 8

[0083]

Table 9

[0084]

Table 10

[0085]

Table 11

[0086]

Table 12

[0087]

Table 13

[0088]

Table 14

[0089]

Table 15

[0090] [Table 16] [Explanation of symbols]

[0091] A Refractory raw material (refractory body) B Carbon fiber fabric x Refractory molded body c. Adhesive b Carbon fiber bundle s1 Refractory working surface s2 Counter moving surface

Claims

1. A method for producing a graphite-containing refractory, comprising embedding a carbon fiber fabric (B) in a graphite-containing refractory raw material (A) by weaving carbon fiber bundles (b) in two or more directions, the method comprising the steps of: A preparation step (i) of applying an adhesive (c) to the carbon fiber fabric (B) so as to cover the outer surface thereof; a molding step (ii) of embedding the carbon fiber fabric (B) to which the adhesive (c) has been attached in the preparation step (i) into a refractory raw material (A) while the adhesive (c) is still adhesive, and molding the refractory raw material (A) in which the carbon fiber fabric (B) is embedded to obtain a refractory molded body (x); The refractory molded body (x) obtained in the molding step (ii) has two or more layers of carbon fiber fabrics (B) embedded in parallel with a gap therebetween, the gap between adjacent carbon fiber fabrics (B) is 10 mm or more, the gap between adjacent carbon fiber bundles (b) in the same direction constituting the carbon fiber fabric (B) is larger than the maximum particle size of the aggregate constituting the refractory raw material (A), and in the cross section of the refractory molded body in the plane direction of the carbon fiber fabric (B), the area ratio of the carbon fiber fabric (B) to the cross-sectional area of ​​the refractory molded body is 40% or more, and the embedded carbon fiber fabric (B) is bonded or adhered to the refractory raw material (A) via an adhesive (c), The carbon fiber bundles (b) in the same direction constituting the carbon fiber fabric (B) have an interval between adjacent carbon fiber bundles (b) that is more than 3 mm and not more than 50 mm, the width of the carbon fiber bundles (b) constituting the carbon fiber fabric (B) is more than 1 mm and not more than 15 mm, and the thickness of the carbon fiber fabric (B) is 0.1 mm or more and 3 mm or less, A method for producing a graphite-containing refractory material, characterized in that the adhesive (c) is a phenolic resin.

2. In the preparation step (i), the adhesive (c) is attached to the outer surface of the carbon fiber fabric (B) and is allowed to penetrate into the bundles of carbon fiber bundles (b) constituting the carbon fiber fabric (B); 2. The method for producing a graphite-containing refractory according to claim 1, characterized in that, in the refractory molding (x) obtained in the molding step (ii), the embedded carbon fiber fabric (B) contains an adhesive (c) in the bundles of carbon fiber bundles (b) and is adhered or in close contact with the refractory raw material (A) via the adhesive (c).

3. 3. The method for producing a graphite-containing refractory according to claim 1, further comprising a drying step (iii) of drying the refractory molded body (x) obtained in the molding step (ii).

4. The method for producing a graphite-containing refractory according to any one of claims 1 to 3, characterized in that in the refractory molding (x) obtained in the molding step (ii), the carbon fiber fabric (B) is embedded along a direction perpendicular to a working surface of the refractory.

5. The method for producing a graphite-containing refractory material according to any one of claims 1 to 4, characterized in that the adhesive (c) contains an organic substance having a residual carbon rate of 6 mass% or more and 80 mass% or less.

6. The method for producing a graphite-containing refractory according to any one of claims 1 to 5, characterized in that the refractory raw material (A) has a graphite raw material content of 1 mass% or more and 80 mass% or less.

7. 7. The method for producing a graphite-containing refractory according to any one of claims 1 to 6, characterized in that the refractory raw material (A) has a magnesia raw material content of 20 mass% or more and 99 mass% or less.

8. The method for producing a graphite-containing refractory according to any one of claims 1 to 7, characterized in that the refractory raw material (A) has an alumina raw material content of 10 mass% or more and 95 mass% or less.

9. The method for producing a graphite-containing refractory according to any one of claims 1 to 6 and 8, characterized in that the refractory raw material (A) has a content of a silica raw material of 1 mass% or more and 50 mass% or less.

10. 10. The method for producing a graphite-containing refractory according to claim 8, wherein the refractory raw material (A) has a content of silicon carbide raw material of 1 mass % or more.

11. The method for producing a graphite-containing refractory according to any one of claims 1 to 10, characterized in that the refractory raw material (A) contains refractory shavings obtained by pulverizing used refractories in an amount of 10 mass% to 90 mass% as the refractory raw material.

Citation Information

Patent Citations

  • Ceramic flamed matter and manufacture

    JP1983026082A

  • Refractory brick

    JP1984156970A

  • Manufacture of ceramic formed body

    JP1987162675A

  • High-strength refractory

    JP1996012456A

  • Refractory having excellent mechanical strength and spalling resistance, and method of manufacturing the same

    JP2005320196A